Electrospun Nano‐CaO2/Polycaprolactone/Gelatin Nanofibers and Their Wound Healing Application through In Situ Supplying H2O2. Issue 4 (13th November 2022) - Qi, Lin; Huang, Yong; Liu, Zheng; Jiang, Yulin; Du, Meixuan; Liu, Limin; Feng, Ganjun; Li, Yubao; Zhang, Li
Abstract: Skin is highly susceptible to foreign pathogens when damaged. Infections usually lead to serious damage to wounds and hinder wound healing, which results in nonhealing and inflammation of the wounds. Herein, a kind of fibrous membrane incorporated with calcium peroxide nanoparticles (n‐CaO2 ) is fabricated by electrospinning the polymer blend solution of polycaprolactone and gelatin. The obtained membranes show a randomly distributed nanofibrous structure with n‐CaO2 particles embedded in each fiber. Such a structure endows the membranes with medium hydrophilicity and improves blood clotting in comparison with the commonly used gauze, while the loading of n‐CaO2 achieves the in situ generation and rapid release of hydrogen peroxide (H2 O2 ), enabling FM‐10 to display a robust bacteria inhibition of over 90% elimination to E. coli . The in vitro cytocompatibility experiment on the fibrous membranes demonstrates low cytotoxicity to L929 fibroblasts. The in vivo assessment indicates that the fibrous membranes can distinctly accelerate the wound healing, of which FM‐5 exhibits the highest wound closure rate (>95%) after 14 days. This study provides a versatile approach, simply by varying the loading dosage of n‐CaO2 into fiber matrix, to fulfill different functions to meet the multiple needs of wound care. Abstract : The novel polycaprolactone (PCL)‐gelatin ultrafine fibers are fabricated by electrospinning, in which the nano‐CaO2 is utilized as functional constituent, for the acceleration of wound healing. The PCL and gelation in the fiber matrix provide robust structure support and biocompatibility, while the embedded n‐CaO2 particles give rise to the in situ release of H2 O2, aiming at the fast antibacterial property.